Pembiasaan Sikap Multikultural Santri Pondok Pesantren Mahasiswa Jagad 'Alimussirry Surabaya - Aini, Aulia Innayatul; Yani, Muhammad Turhan (Kajian Moral dan Kewarganegaraan, 2025)
Pondok Pesantren Mahasiswa Jagad 'Alimussirry is an Islamic educational institution that has a heterogeneous environment. This Islamic boarding school is a combination of traditional and modern Islamic boarding schools, based on Nahdhiyyin whose students come from students. The students of this Islamic boarding school come from various regions, including Madura, Nganjuk, Mojokerto, Pasuruan, Madiun, South Tangerang, Gresik, Lamongan, Semarang and so on. The purpose of this study was to identify the urgency and habituation of multicultural attitudes of students at Pondok Pesantren Mahasiswa Jagad 'Alimussirry. The approach used is descriptive qualitative with a case study research design. This research was conducted at Pondok Pesantren Mahasiswa Jagad 'Alimussirry located on Jl. Jetis Kulon VI/16A Wonokromo and Jl. Ketintang Timur PTT VB No. 3-4, Surabaya. The informants in this study were the director, administrators of the boarding school, ustadz/ustadzah, and the students. Data collection methods include participatory observation, in-depth interviews, and documentation. Data analysis is carried out through a series of stages, such as data collection, data reduction, data presentation, and drawing conclusions. The research findings show that the habituation of multicultural attitudes by students carried out at the Pondok Pesantren Mahasiswa Jagad 'Alimussirry can be seen through four categories, including inclusive-pluralist attitudes (daily study activities, yasiin tahlil, halal bihalal); democratic attitudes (daily study activities, student regulation forums, sholawatan activities); humanist attitudes (the Prophet Muhammad's birthday, the August 17 independence ceremony, and the student day ceremony); and tolerance attitudes (daily study activities, congregational prayers, student regulation forums). The importance of habituating multicultural attitudes among students focuses on efforts to prevent conflict and discrimination, strengthen humanitarian values ​​and unity, foster a sense of compassion and mutual respect, maintain harmony, and increase students' sensitivity to the diversity of society.